The Effect Of Regional Native Income And Capital Expenditure On Regional Financial Independence In District /City Goverments In West Java Province Year 2016 -2020 - Akbar, Akhmad (Publisher Cv. Inara, 2022)
The purpose of this study is to find out the influence of Regional Native Income and Capital Expenditures partially and simultaneously on Regional Financial Independence in Regency / City Governments in West Java Province in 2016-2020. This research uses quantitative methods. The sampling technique in this study used census methods (saturated samples) from 27 district/city samples with observation years for 5 years from 2016-2020 with a total of 135 observation data. The statistical analysis of the data used in this study is the regression analysis of panel data with Eviews 9. The results of the research obtained showed that the original income of the region and capital expenditures were able to explain the financial independence of the region by 99.36%, while the remaining 0.64% was explained by other variables outside the study.The results of the partial test showed that the original income of the region had a significant positive effect on regional financial independence, while capital expenditure had no effect on regional financial independence. The results of the test simultaneously, showed that the original income of the region and capital expenditures affected the financial independence of the region.